THE INFLUENCE OF FIELD WORK PRACTICES ON THE WORK READINESS OF VOCATIONAL HIGH SCHOOL (SMK) STUDENTS - HR. Hasiib Hikmal Abrar Manaf; Ilhan Widiasaputra; Achmad Irfan Dwi Cahyono; Achmad Nur Hasyim (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
This research aims to determine (1) the effect of practical work experience on job readiness, (2) the effect of confidence on job readiness, (3) the effect of practical work experience and self-confidence on job readiness. The population in this study is the students of SMK Negeri 15 Samarinda, and the sample in this study is the students who are taking the automotive major and have completed practical work, totaling 82 people, consisting of three classes: OT1 with 29 people, OT2 with 25 people, and OT3 with 28 people. The results of this study are (1) Practical Work Experience has a positive and significant effect on the Work Readiness of SMA 15 Samarinda students. (2) Confidence does not have a significant relationship with the Work Readiness of SMA 15 Samarinda automotive major students as indicated by the major. (3) Work experience and self-confidence simultaneously have a positive and significant effect on the work readiness of students at Vocational High School 15 Samarinda in the automotive field